Hubungan Indeks Massa Tubuh Dengan Kejadian Dismenore Pada Remaja Putri Di Pondok Pesantren Nurul Islam Jember - Karomah, Ilmiyatul; Maryanti, Syiska Atik; Bachri, Syaiful (Jember Maternal and Child Health Journal, 2024)
Background: BMI associated with the presence of fat can increase prostaglandins which cause dysmenorrhea. Dysmenorrhea is a problem that can arise due to high fat which can increase prostaglandins, causing pain. Dysmenorrhea can interfere with daily activities, especially decreased learning productivity which results in decreased achievement. Dysmenorrhea is included in the risk group so reducing dysmenorrhea is considered important. Purpose: Analyzing the relationship between Body Mass Index and the incidence of dysmenorrhea in young women at the Nurul Islam Islamic Boarding School, Jember. Methods: This study used an observational method with a cross sectional approach. The population of all class X teenage girls is in the Nurul Islam Jember Islamic Boarding School. The sample size was 74 young women who were taken by simple random sampling, by distributing questionnaires and then measuring height and weight. Results: This study shows that most of the young women at the Jember Nurul Islam Islamic Boarding School have an abnormal BMI of 66.21% and 54.1% of them experience dysmenorrhea. Statistical test results show a relationship between BMI and the incidence of dysmenorrhea in young women at the Nurul Islam Jember Islamic Boarding School. Conclusion: In this study, if the BMI was underweight, overweight and obese, the dysmenorrhea score would be high, conversely if the BMI was normal, the dysmenorrhea score would decrease. It is hoped that for health services, it is hoped that it can improve the performance of UKS staff in preventive promotive efforts regarding the incidence of dysmenorrhea in young women such as providing information in the health unit which contains nutrition intake.